Hepatic-to-azygos vein redirection after a failed bifurcated graft Fontan conversion. Issue 4 (5th April 2023) - Koizumi, Junichi; Ikai, Akio; Iwase, Tomoyuki; Kin, Hajime
Abstract: A successful hepatic-to-azygos vein redirection was performed in a patient with absent inferior vena cava using a long vascular graft to address a pulmonary arterio-venous fistula after a failed Fontan conversion. No exacerbation was observed 5 years postoperatively. Abstract : Pulmonary arterio-venous fistula (PAVF) is a well-known complication in patients with absent inferior vena cava (IVC) [1].